Cy Twombly: Sign, Meta-Sign and Sense - Johanna Malt (Sillages Critiques)
In a 1979 article on the work of the American painter Cy Twombly, Roland Barthes writes “TW [Twombly] refers to writing (as he also often refers to culture, through words), and then he goes off somewhere else.” This article starts from the question of where or what this “somewhere else” might be, towards which Cy Twombly heads on leaving behind cultural and linguistic meaning. I propose that it is towards something logically prior to, on in a sense “behind” signification that Cy Twombly directs his attention, and that phenomenology offers us a way of approaching this ground. Via an analysis of the effect of layering in several paintings from the early 1960s, I argue that, in this layering, signification via the presence of text becomes just another category of object to be called forth, or rather, another mode of relation to the world which the painting investigates in its meta-reflection on relationality as meaning.